Oxytocin Release Increases With Age and Is Associated With Life Satisfaction and Prosocial Behaviors - Zak, Paul J.; Curry, Ben; Owen, Tyler; Barraza, Jorge A. (Frontiers in Behavioral Neuroscience, 2022)
Helping behaviors and life satisfaction generally increase after middle-age. The neural substrates of prosocial behaviors in older adults may offer additional insights into these changes over the lifespan. The present study examines the endogenous release of the neuromodulator oxytocin (OT) in participants aged 18-99 and its relationship to prosocial behaviors. OT has been shown to influence trust, altruism, charity, and generosity, yet the effect of age on OT release has not been well-established. Blood samples before and after a video stimulus were obtained from 103 participants in order to examine the impact of OT on prosocial behaviors. We found that OT release following a social prime increased with age (r=0.49, p=0.001) and that OT moderated the relationship between age and donations to charity. We tested for robustness by examining three additional prosocial behaviors, money and goods donated to charity during the past year and social-sector volunteering. OT moderated the impact of age on all three prosocial behaviors (ps<.05). The analysis also showed that participants' change in OT was positively associated with satisfaction with life (p=0.04), empathic concern (p=0.015), dispositional gratitude (p=0.019), and religious commitment (p=0.001). Our findings indicate that the neural chemistry that helps sustain social relationships and live a fulfilled life appear to strengthen with age.